PENGARUH KETERAMPILAN MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA DENGAN PEMANFAATAN FASILITAS BELAJAR SEBAGAI VARIABEL MODERATOR DALAM MATA PELAJARAN EKONOMI (Survei pada siswa kelas XI IIS SMA Negeri kota Bandung) - Cyndy Andriana, - (2021)
This research is based on the low students' learning outcomes in economic subjects in high schools in the City of Bandung which are not optimal yet, as evidenced by the odd Final Semester Assessment (PAS) for the 2019/2020 school yea which still many students have scores less than the Minimum Mastery Criteria (KKM). The purpose of this study was to determine the effect of teacher teaching skills on the level of student learning outcomes in economic subjects by using learning facilities as a moderator variable. The population in this study was 400 students of class XI IIS SMA Negeri in Bandung with stratified random sampling technique. The data Analysis technique used a simple regression anaylisis and regretion of moderation variables. The results of this study indicate; (i) (i) Teachers' teaching skills are in the high category; student learning outcomes in the high category; and utilization of learning facilities in the high category; (ii) there is an effect of teacher teaching skills on students' learning outcomes; (iii) the level of utilization of learning facilities fully moderates the level of teaching skills of teachers on students' learning outcomes, the use of learning facilities is a pure moderator.